Rehabilitation of abandoned housing projects of housing developer companies under receivership in Peninsular Malaysia: Some salient issues and suggestions - Md Dahlan, Nuarrual Hilal (Sweet & Maxwell Asia, 2012)
Abandoned housing projects are one of the main problems in the housing industry in Peninsular Malaysia.Even though the Malaysian government has provided laws and policies to govern the housing industry to protect the interests of all parties in the industry, yet the problem of abandoned housing projects is still an unsettled issue until today.The real victims are the purchasers themselves.Usually when a housing developer company is under receivership, the affairs and business of the company are taken over by the appointed receiver and manager, pursuant to the terms in the deed of debentures. The receiver and manager may rehabilitate the abandoned projects left by the housing developer companies, if the projects are viable for rehabilitation, with the approval of the debenture holders.Otherwise,if the project is not viable, particularly because there are insufficient funds to run the intended rehabilitation or the problems relating to the abandoned housing projects are too great to settle, the project may be stalled forever without any prospect for rehabilitation, to the detriment of the purchasers.This article discusses the law and practice in the rehabilitation of abandoned housing projects in Peninsular Malaysia of the housing developer companies, under receivership.This writing finds that there are certain lacunae in the law and practice in dealing with the problems of abandoned housing projects particularly in respect of rehabilitating the projects and protecting the purchasers' rights and interests.Further, it is submitted that the recent proposed amendments to the Housing Development (Control and Licensing Act 1966 (Act 118) and the Corporate Law Reform Committee's ("CLRC" recommendations also are still inadequate to face the problems of abandoned housing projects.In the final part of this article the author proposes certain suggestions for facing the problems of abandoned housing projects of the housing developer companies under receivership and their rehabilitation in Peninsular Malaysia in order to improve the law and practice regulating housing industry against abandonment of housing projects in Peninsula Malaysia.